Studies of Genetic Diversity in a Homogeneous Population of Withania Somnifera (L.) Dunal using DNA Based Markers - Singh, Ruchika (My University, 2023)
Withania somnifera (L.) Dunal (2n=48) family Solanaceae is an important medicinal plant that contains many active ingredients used to treat various ailments. Most of the wild population are seed raised and show a great deal of variations in active ingredients which could be due to (i) genetic variations and (ii) environmental effects. The aim of the present study is to investigate the genetic diversity in these seed raised plants of W. somnifera using morphological and molecular markers (Random Amplified Polymorphic DNA: RAPD, Inter Simple Sequence Repeats: ISSR and start codon targeted polymorphism: SCoT). Morphological studies revealed that the leaves were oval or oblong in shape having pinnate venation. The average leaf length and width recorded were 6.06 cm and 4.15 cm respectively. The average internodal distance recorded was 3.39 cm and in an average 5-6 berries were recorded in a cluster. This data provided limited morphological variations among plants. Therefore, PCR based amplification of RAPD, ISSR and SCoT makers was caried out using isolated DNA of selected plants. RAPD primers amplified 95 band out of which 94 were polymorphic (98%), followed by ISSR which amplified 245 band and 229 were polymorphic (93.6%). The SCoT primers produced 200 bands out of which 118 were polymorphic (56.6%) thereby detecting least polymorphism among the three markers. The dendrogram constructed grouped the 12 plants in 2 clusters, in case of ISSR plant WS 12 was out grouped whereas dendrogram constructed based on the combined data of all three molecular markers out grouped WS 06 plant. The PCA analysis for RAPD and ISSR recorded 27.2%, 12.8% and 36.5%, 9.8% component variance respectively. This study suggests that RAPD marker were more efficient in the detection of polymorphism in W. somnifera population. The information gathered here might be used to develop conservation plans and routine maintenance strategies for this population.
Keywords: RAPD marker; ISSR marker; Ashwagandha; medicinal plant